ӘЖИНИЯЗДЫҢ ЖАСЛАРҒА БИЛИМ БЕРИЎ УСЫЛЛАРЫ ҲАҚҚЫНДА - Таспанова, Ж.К. (SCIENCE and SOCIETY, 2020)
The article deals with the role of issues of education and upbringing in the works of the famous Karakalpak poet-classic of the XIXth century Ajiniyaz Kosibay uli. The ideas of the poet about methods of teaching and upbringing of young generation are still of a great importance and can be applied today.